2017
DOI: 10.1101/212431
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic variation across the human olfactory receptor repertoire alters odor perception

Abstract: The human olfactory receptor repertoire is characterized by an abundance of genetic variation that affects receptor response, but the perceptual effects of this variation are unclear. To address this issue, we sequenced the OR repertoire in 332 individuals and examined the relationship between genetic variation and 276 olfactory phenotypes, including the perceived intensity and pleasantness of 68 odorants at two concentrations, detection thresholds of three odorants, and general olfactory acuity. Genetic varia… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 51 publications
1
33
1
Order By: Relevance
“…More recently, the specific amino acid residues of OR5AN1 that are responsible for its high selectivity to musk-smelling chemicals have also been confirmed (Ahmed et al, 2018). These studies were possible owing to three types of information: (1) perceptual responses of humans, (2) the odorant receptors that detect the chemicals from heterologous expression systems, and (3) genetic studies (Trimmer et al, 2019). Obtaining this information is not trivial for reasons that include the difficulty of receptor deorphanization and that behavioral responses are known for only a fraction of the purported volatile space, owing to low throughput data collection with human volunteers.…”
Section: Introductionmentioning
confidence: 95%
“…More recently, the specific amino acid residues of OR5AN1 that are responsible for its high selectivity to musk-smelling chemicals have also been confirmed (Ahmed et al, 2018). These studies were possible owing to three types of information: (1) perceptual responses of humans, (2) the odorant receptors that detect the chemicals from heterologous expression systems, and (3) genetic studies (Trimmer et al, 2019). Obtaining this information is not trivial for reasons that include the difficulty of receptor deorphanization and that behavioral responses are known for only a fraction of the purported volatile space, owing to low throughput data collection with human volunteers.…”
Section: Introductionmentioning
confidence: 95%
“…It is clear that these olfactory receptors (ORs) play a key role in odorant perception. Up to now, for approximately 40% of the 400 functional human ORs, agonists have been identified in bioassays [ 18 ]. Research on structure–activity relationships of the human OR10G receptors has shown that these receptors are broadly tuned to volatile phenols ( Table 1 ) [ 19 ].…”
Section: Perception Of Odor-active Phenolsmentioning
confidence: 99%
“…Odor percepts arise from the pattern of activation across these different receptors (see [ 9 ] for a review). The specific receptors present in an individual’s nose and the number of each type of receptor are genetically determined, resulting in individual differences in odor perception [ 10 , 11 ]. That is, some individuals may lack a functional variant of a certain receptor and be unable to smell molecules that would bind to that receptor, while still having an otherwise normal sense of smell.…”
Section: Introductionmentioning
confidence: 99%